Propuesta arquitectónica para un terminal de transporte mixto en Neiva (Huila) (2020)
In the world there is an immense variety of means of transport that are important for the day to day mobility of cities or communities, these have been advancing technologically in order to maintain comfort to users and offer a better quality of service and I also make progress in the adaptation of the collection points where you will start your trip to the destination point. There are very particular means of transport and are considered cultural heritage, as it is on this occasion, a peculiar means of transport and that exists in a few parts of the world, “The Bus Ladder or Chiva” as it is called in these cities to refer to these vehicles. In this way, taking into account the objective of this research, finding and studying the factors, the importance and consequences of this means of transport to the city and society. Therefore, in order to solve the problems and consequences that are found below, an architectural project of the expansion of the current transport terminal is proposed to incorporate the bus or escalator type of chiva and agricultural trade in order to solve the problem. The inconveniences found and in the same way tie the positive factors that carry this means of transport to rural communities. This in order to provide security to the users of this means of transport to the owners of these vehicles and to the passers-by who passed through these sectors, in addition to a spatial order for the organization of these activities.